Comparison of different ovulation protocols in patients undergoing controlled ovulation hyperstimulation with intra uterine insemination - Kurian, Shirly; Battina, Sarat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: For many couples’ advent of a baby is the most beautiful gift of life. Involuntary childlessness by itself does not threaten physical health but can have a strong impact on the psychological and social wellbeing of couples. The aim of the present investigation was comparison of different ovulation protocols in patients undergoing controlled ovulation hyperstimulation with Intra uterine insemination. Methods: A Prospective observational study was conducted in the department of obstetrics and gynaecology. 200 couples who underwent 541 cycles with controlled ovarian hyperstimulation. Variables selected for analysis were female age, menstrual history, duration of infertility, number of cycles, number dominant follicle diameter, endometrial thickness. Results: Maximum patients underwent ovulation induction with clomiphene citrate (202/541) and then with letrozole (202/541). Conclusions: Nowadays when the costs of health care are limited, intrauterine insemination can hold its place as a low-cost method of infertility treatment. Conclusively with careful selection of subjects, appropriate controlled ovarian stimulation and intra uterine insemination, good pregnancy rates with low multiple pregnancy rates can be achieved.